2009
DOI: 10.1016/j.neuron.2009.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Rapidly Adapting Mechanoreceptors and Their Developmental Dependence on Ret Signaling

Abstract: In mammals, the first step in the perception of form and texture is the activation of trigeminal or dorsal root ganglion (DRG) mechanosensory neurons, which are classified as either rapidly (RA) or slowly adapting (SA) according to their rates of adaptation to sustained stimuli. The molecular identities and mechanisms of development of RA and SA mechanoreceptors are largely unknown. We found that the “early Ret+” DRG neurons are RA mechanoreceptors, which form Meissner corpuscles, Pacinian corpuscles and longi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
337
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 210 publications
(360 citation statements)
references
References 55 publications
(93 reference statements)
18
337
1
Order By: Relevance
“…These sensory abnormalities may be comparable with neuropathic pain in the somatosensory system. We found that endogenous GDNF induced basal firing at low frequencies ϳ0.1 Hz or less in touch-sensitive or RA mechanoreceptive fibers, which are characterized by the expression of RET during a developmental period (Bourane et al, 2009;Luo et al, 2009). We confirmed that GDNF and GFR␣1 were present in Meissner corpuscles.…”
Section: Basal Firing In Sensory Nervessupporting
confidence: 72%
See 1 more Smart Citation
“…These sensory abnormalities may be comparable with neuropathic pain in the somatosensory system. We found that endogenous GDNF induced basal firing at low frequencies ϳ0.1 Hz or less in touch-sensitive or RA mechanoreceptive fibers, which are characterized by the expression of RET during a developmental period (Bourane et al, 2009;Luo et al, 2009). We confirmed that GDNF and GFR␣1 were present in Meissner corpuscles.…”
Section: Basal Firing In Sensory Nervessupporting
confidence: 72%
“…Because the basal firing was found in touch-sensitive or rapidly adapting (RA) mechanoreceptive fibers, it may be produced by a mechanism specific to RA mechanoreceptive fibers. RA mechanoreceptive neurons in the dorsal root ganglia or trigeminal ganglia are characterized by the expression of the receptor tyrosine kinase RET during a certain developmental period (Bourane et al, 2009;Luo et al, 2009). RET is a component of the GDNF family receptors.…”
Section: Somatic Cortical Potentiation After Peripheral Nerve Cuttingmentioning
confidence: 99%
“…Within the central nervous system, we analyzed the brain, as signaling via Ret is important for the survival of central noradrenergic neurons and dopaminergic neurons in the ventral midbrain, as well as the spinal cord, where GDNF/ GFR␣1/Ret signaling is critical for axon guidance into the hind limbs and survival of ␥ motor neurons (16 -21). In the peripheral nervous system, we analyzed sensory neurons of the dorsal root ganglia (DRG), where neurturin/GFR␣2/Ret signaling is important for the survival and maintenance of mechanoreceptors during development (22,23). Additionally, shortly after birth, a subclass of nociceptors transition from being TrkApositive to expressing GFR␣1/Ret to support the development and survival of nonpeptidergic nociceptors (24 -26).…”
Section: Exon Skipping Creates Large Deletions In the Extracellularmentioning
confidence: 99%
“…Ret expression appears early during development of mechanoreceptors, and in the absence of Ret, cutaneous mechanoreceptive end-organs are underdeveloped and Pacinian corpuscles are absent. 15,16 The transcription factor short stature homeobox 2 (Shox2) promotes TrkB expression in mechanoreceptors, and Shox2 is required for formation of most TrkB+ neurons. Consistent with this, Shox2 mutants have a deficit in a subset of mechanoreceptors that terminate in Meissner corpuscles and Merkel cells, and light touch sensation is strongly impaired.…”
Section: Molecular Mechanisms Of Mechanoreceptor Developmentmentioning
confidence: 99%
“…Interestingly, c-Maf is essential for appropriate expression of Ret, and the morphology of rapidly adapting mechanoreceptors in Ret mutant mice resemble those observed in c-Maf mutants. 15,16,20 Several deregulated genes encode potassium channels; among these Kcnq4 is already known to affect firing properties of rapidly adapting mechanoreceptors and contributes to the changes observed in c-Maf mutants. 20,23 MafA is co-expressed with c-Maf in rapidly adapting mechanoreceptors and the two closely related factors might act redundantly.…”
mentioning
confidence: 99%